Defining the core microbiome of the symbiotic dinoflagellate, Symbiodinium. Issue 1 (1st December 2017) - Lawson, Caitlin A.; Raina, Jean‐Baptiste; Kahlke, Tim; Seymour, Justin R.; Suggett, David J.
Summary: Dinoflagellates of the genus Symbiodinium underpin the survival and ecological success of corals. The use of cultured strains has been particularly important to disentangle the complex life history of Symbiodinium and their contribution to coral host physiology. However, these cultures typically harbour abundant bacterial communities which likely play important, but currently unknown, roles in Symbiodinium biology. We characterized the bacterial communities living in association with a wide phylogenetic diversity of Symbiodinium cultures (18 types spanning 5 clades) to define the core Symbiodinium microbiome. Similar to other systems, bacteria were nearly two orders of magnitude more numerically abundant than Symbiodinium cells and we identified three operational taxonomic units (OTUs) which were present in all cultures. These represented the α‐proteobacterium Labrenzia and the γ‐proteobacteria Marinobacter and Chromatiaceae . Based on the abundance and functional potential of bacteria harboured in these cultures, their contribution to Symbiodinium physiology can no longer be ignored.